Comparison of TNF-α levels before and after treatment in patients with periodontitis with and without type 2 diabetes mellitus - Varshney, Amitabh; Sharma, Shivani; Garg, Lavisha; Mishra, Shweta; Bansal, Amish; Singh, Padam (Journal of Neonatal Surgery, 2025)
Background: Periodontitis is an inflammatory reaction triggered by the pathogenic microorganisms present in a chronic dental biofilm, which leads to progressive harm to the structures that support teeth. The present study was conducted to compare TNF-α levels before and after treatment in patients with periodontitis with and without type 2 diabetes mellitus. Materials & Methods:80 patients were divided into 2 groups of 40 each. Group I were periodontitis and group II were periodontitis+ type 2 diabetes mellitus patients. Group I were further subdivided into group A who underwent scaling and root planing alone and group B who underwent scaling and root planing+ low level laser therapy. Group II were further subdivided into group C who underwent scaling and root planing alone and group D who underwent scaling and root planing+ low level laser therapy. In both groups, saliva was collected in a test tube for the assessment of TNF-α levels at baseline and at 8 weeks. Results: Group A had 1 male and 9 females, group B had 10 males and 10 females, group C had 8 males and 12 females and group D had 9 males and 11 females. The mean age was 45.2±5.2 years, 47.4±5.8years, 46.3±5.1 years and 45.8±3.8 years in group A, B, C and D respectively. The mean BMI was 24.2±3.6 Kg/m2, 23.2±4.1 Kg/m2, 23.1±4.3 Kg/m2 and 22.5±6.1 Kg/m2 in group A, B, C and D respectively. At baseline and 8 weeks, in group A, PI was 1.71, 0.67, BI was 1.92 and 0.48, PD was 6.2 and 2.9 and CAL was 6.5 and 2.5 respectively. In group B, PI was 1.72 and 0.68, BI was 2.1 and 1.4, PD was 5.4 and 2.9 and CAL was 2.8 and 2.7 respectively. In group C, PI was 2.1 and 0.37, BI was 1.94 and 0.41, PD was 5.8and 3.2 and CAL was 6.1 and 3.1 respectively. In group D, PI was 2.1 and 0.4, BI was 1.7 and 0.42, PD was 5.7 and 2.7 and CAL was 5.8 and 2.6 respectively. The difference was significant (P< 0.05). TNF- α at baseline and at 8 weeks in group A was 14.2 ±2.3 and 9.1±1.1, in group B was 14.9±5.3 and 10.5±4.2, in group C was 22.3±7.1 and 14.8±7.2 and in group D was 22.1±8.4 and 12.4±3.1 respectively. The difference was significant (P< 0.05). Conclusion: Salivary TNF-α levels in periodontitis are associated with T2DM. There was a notable improvement in both clinical and salivary TNF-α levels with SRP and SRP adjunct to LLLT.